2018
DOI: 10.1021/acssuschemeng.7b04716
|View full text |Cite
|
Sign up to set email alerts
|

Renewable (Bis)pyrrolidone Based Monomers as Components for Thermally Curable and Enzymatically Depolymerizable 2-Oxazoline Thermoset Resins

Abstract: In this study we describe the synthesis of bis(pyrrolidone) based dicarboxylic acids from itaconic acid and their application in 2-oxazoline resins for fully renewable thermoset materials. The monomers are obtained using a bulk aza-Michael addition of a diamine and two itaconic acid molecules using a catalytic amount of water. The monomers can be isolated in high purity after recrystallization, though their yield proved to be highly dependent on the selected diamine spacer length: In general, only the dicarbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 68 publications
1
32
0
Order By: Relevance
“…It is a renewable unsaturated dicarboxylic acid, rated by the U.S. Department of Energy as one of the twelve most important biomass‐derived compounds that can be transformed into a wide range of valuable chemicals or materials . IA is a key substrate for production of aliphatic, unsaturated and saturated polyesters, degradable polyamides as well as condensation polymers bearing pyrrolidine ring in the main chain . The acid is also a well‐known low reactive vinyl monomer, and its free radical polymerization typically requires long reaction times and high amounts of an initiator .…”
mentioning
confidence: 99%
“…It is a renewable unsaturated dicarboxylic acid, rated by the U.S. Department of Energy as one of the twelve most important biomass‐derived compounds that can be transformed into a wide range of valuable chemicals or materials . IA is a key substrate for production of aliphatic, unsaturated and saturated polyesters, degradable polyamides as well as condensation polymers bearing pyrrolidine ring in the main chain . The acid is also a well‐known low reactive vinyl monomer, and its free radical polymerization typically requires long reaction times and high amounts of an initiator .…”
mentioning
confidence: 99%
“…The BP-C 2 percentage incorporated in the polymer was determined from the ratio between the integral of signal β and the integral of the resonance corresponding to the methylene protons next to the carbonyl signal of the sebacic acid moiety (resonance A), as shown in Figure 1 and Figure S1. Note, the signal for protons δ split up into three peaks as a result of the different rotational conformations of the pyrrolidone rings and the corresponding interactions of the protons δ with the carbonyl in the pyrrolidone rings [25]. The 1 H NMR traces used for the determination of the BP-C 2 percentage of the other polymers are provided in the Supplementary Materials.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the aza-Michael addition between the α,β-unsaturation of itaconic acid with an alkyl-amine can be used to generate renewable pyrrolidone-based dicarboxylic acid (BPDA) monomers. In turn, these BPDA monomers have successfully been used for the synthesis of polyesters [18,19], polyamides [20,21,22,23], and poly(ester-amide)s [24,25,26]. Though the presence of the cyclic pyrrolidone moieties are generally used to enhance the glass transition temperature [18], they also enhance the polymer’s affinity to water, resulting in an increased moisture uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, BPDA monomer based on 1,10-dodecanediamine ( c ) was co-polymerized into poly(ester amide)s with sebacic acid, 1,10-dodecanediamine, and 1,4-butanediol, where it was shown that adding BPDA monomer could suppress crystallization (Wang et al, 2016). BPDA monomers based on aliphatic diamines ( c , e.g., is 1,2-ethylene diamine or 1,12-dodecanediamine) can be polymerized with various bis(2-oxazoline)s ( h , e.g., Y is 2,5-furan or 1,3-phenylene) to yield linear or cross-linked amorphous poly(ester amide)s with a T g ranging from 60 to 120°C (Roy et al, 2018, 2019).…”
Section: State Of the Artmentioning
confidence: 99%